Electron-hopping across dye-sensitized mesoporous NiO surfaces. Issue 48 (5th December 2022) - Wrede, Sina; He, Lanlan; Boschloo, Gerrit; Hammarström, Leif; Kloo, Lars; Tian, Haining
Abstract : Electron hopping across dye-sensitized mesoporous NiO surfaces was investigated, showing that the electron hopping between NiO surface states is much faster than between the dyes. Abstract : To gain a deeper understanding of the underlying charge processes in dye sensitized photocathodes, lateral electron hopping across dye-sensitized NiO photocathodes was investigated. For dye-sensitized systems, hole hopping across photoanodes has been studied extensively in the literature but no expansive studies on electron hopping in sensitized photocathodes exist today. Therefore, an organic p-type dye (TIP) with donor–linker–acceptor design, showing high stability and electrochemical reversibility, was used to study the electron transfer dynamics (electron-hopping) between dyes with temperature dependent spectroelectrochemistry and computational simulations. Besides intermolecular electron-hopping across the surface with a rate constant in the order of 10 5 s −1, our results show a second electron hopping pathway between NiO surface states with a rate constant in the order of 10 7 s −1, which precedes the electron hopping between the dyes. Upon application of a potential step negative enough to reduce both the dye and NiO surface states, the majority of NiO surface states need to be reduced before intermolecular electron transfer can take place. The results indicate that, in contrast to sensitized photoanodes where intermolecular charge transfer is known to influence recombination kinetics, intermolecular charge transport processes in TIP dye sensitized NiO photocathodes is less relevant because the fast electron transport between NiO surface states likely dominates recombination kinetics.